Phosphomolybdic Acid-Doped Zeolitic Imidazolate Framework-8 Hybrid: Nanostructured Material with Synergistic Antibacterial Effect - Abdelkhalek, Mariam Mohammad (AUC Knowledge Fountain, 2024)
Bacterial infections represent a major global health concern, causing millions of deaths and significant economic burdens. The development of nanostructured surfaces with antibacterial activity can revolutionize infection control practices. In this study, a hybrid material of Zeolitic imidazolate framework-8 (ZIF-8) doped with phosphomolybdic acid (PMA) was synthesized and characterized by FESEM, EDS, XRD, FTIR, and N2 sorption isotherm. The antibacterial activity against Escherichia coli as a model organism was tested by colony forming unit (CFU) reduction assay, minimum inhibitory concentration (MIC), and time-kill curve. PMA@ZIF-8 performance as an antibacterial agent was superior to its individual constituents, suggesting synergistic effect of PMA and ZIF-8. The incorporation of PMA into the ZIF-8 significantly enhanced its antibacterial efficacy, as evidenced by a twofold reduction in MIC (375 μg/mL vs. 750 μg/mL) and a 4.35 times increase in bactericidal kinetics rate constant. The time-kill curve experiment revealed that PMA@ZIF-8 achieved a 3-log reduction within 7 hours, whereas ZIF-8 required 24 hours to reach the same level of reduction. Density functional theory (DFT) was employed to conduct a quantum mechanical simulation. The density of states and bandgaps of ZIF-8 and PMA@ZIF-8 revealed a significant decrease in the bandgap in the hybrid, and powerful reactive oxygen species generation with subsequent bacterial death. Accordingly, PMA@ZIF-8 can be computationally featured as an oxidative nanozyme. PMA@ZIF-8’s surface topology revealed nanorods protrusions, suggesting potential mechano-bactericidal effect. This study highlights the potential of PMA@ZIF-8 hybrid as a highly effective antibacterial agent, demonstrating its superior performance compared to its individual constituents and suggesting synergistic effects. The nanostructured surfaces with enhanced antibacterial activity hold promise for creating multifunctional antibacterial surfaces.